DIFFERENCE BETWEEN PUBLIC HEALTH AND HEALTHCARE MANAGEMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Public health management covers the administrative and managerial capacities, organizational structures, and systems needed to finance and deliver health services more efficiently, effectively, and equitably public financial management (pfm) health systems rely on pfm to be effective, efficient, and accountable